Teaming with Technology at the TSA: An Examination of Trust in Automation's Influence on Human Performance in Operational Environments. (September 2018) - Korbelak, Kristopher; Dressel, Jeffrey; Tweedie, Donald; Wilson, Whitney; Erchov, Simone; Hilburn, Brian
Automated systems are not only commonplace but a necessity to complete highly specialized tasks in many operational environments. Problems arise, however, when the automation is used injudiciously. Trust is known to influence how workers use and rely on automated systems, especially when the operational environment poses a great amount of complexity for the user. The environment in which most Transportation Security Administration (TSA) workers operate is characterized by complexity that often demands the use of automation to complete required tasks. The TSA aims to better understand the influence of trust in automation on operational performance to better support its mission and workforce. This paper will discuss the methods, findings, and practical implications gleaned from an examination of the role trust plays on human-automation interactions in the operational environment at TSA.